Answers:
1. x = 2 is solution of both equations.
2. x = 3 is a solution of equation b.
3. x = -2 is solution of both equations.
4. x = -1 is solution of both equations.
5. x = -5 is solution of both equations.
Step-by-step explanation:
To know if the value of x is a solution, we need to replace x with the given value. So:
1. Repalcing x by 2, we get:
a. x ( 2 + 3) = 10
2 ( 5) = 10
10 = 10
b. 2x + 3x = 10
2(2) + 3(2) = 10
4 + 6 = 10
10 = 10
The equality is true in both cases, so x = 2 is solution of both equations.
2. Replacing x by 3, we get:
a. x - 4 = 1
3 - 4 = 1
- 1 = 1
b. 4 - x = 1
4 - 3 = 1
1 = 1
Since -1 and 1 are distintc, x = 3 is a solution of equation b.
3. Replacing x by -2, we get:
a. 7x = -14
7(-2) = -14
- 14 = - 14
b. x(14) = - 28
(-2)(14) = - 28
- 28 = - 28
So, x = -2 is solution of both equations.
4. Replacing x by -1, we get:
a. x + 3 = 2
-1 + 3 = 2
2 = 2
b. 3 + x = 2
3 + (-1) = 2
2 = 2
So, x = -1 is solution of both equations.
5. Replacing x by -5, we get:
a. 3 - x = 8
3 - ( - 5) = 8
3 + 5 = 8
8 = 8
b. 5 - x = 10
5 - ( - 5) = 10
5 + 5 = 10
10 = 10
So, x = -5 is solution of both equations.